Art 2044 Systematic Literature Review: Mubadalah in the Right to Maintenance from the Perspective of Islamic Family Law - Bidayatul Inayah; Itang; Dede Permana; Aspandi; Wasehudin; Sayehu (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
Mubadalah in the husband-wife relationship has significant relevance in the context of Islamic family law which continues to develop. Understanding each person's duties and responsibilities is very important considering social changes and increasing demands for more equal and harmonious interactions in family life. This paper aims to analyze mubjadi from the perspective of Islamic family law, which emphasizes the importance of equality and mutual understanding between husband and wife in creating a just and harmonious family. Specifically, this study discusses the right to maintenance as one of the fundamental aspects in husband-wife relations, including its meaning, implementation, and responsibility for fulfilling it from a mubadalah perspective. The method used in this research is a systematic literature review based on big data via publish or perish Google Scholar and publish or perish crossref with VOS viewer visualization. The results of the discussion in this paper are on the application of the concept of mubindah in husband-wife relationships, the urgency of equality of rights and obligations, and its impact on domestic life